The $n$-th harmonic number is defined as $$ H_n=\sum_{k=1}^{n}\frac{1}{k}, $$ and the generalized harmonic numbers are defined by $$ H_{n}^{(r)}=\sum_{k=1}^{n}\frac{1}{k^r}. $$ Recently, I have found the following combinatorial identity involving the second-order harmonic numbers (I have computational evidence).

Question: \begin{align} \sum_{s=0}^{m}{2s\choose s}{s\choose m-s}\frac{(-1)^s }{s+1}H_{s}^{(2)}=\frac{2(-1)^m}{m+1}\sum_{s=0}^m H_{s}^{(2)}. \end{align} Is this a known combinatorial identity? Any proof or reference? However, if I replace $H_s^{(2)}$ by other generalized harmonic numbers in the above identity, I can not find some similar identities.

Note: This combinatorial identity was motivated by the following identity \begin{align} \sum_{s=0}^{m}{2s\choose s}{s\choose m-s}\frac{(-1)^s}{s+1}=(-1)^m. \end{align} One can refer to How to prove $\sum_{s=0}^{m}{2s\choose s}{s\choose m-s}\frac{(-1)^s}{s+1}=(-1)^m$?

I appreciate any hints, pointers etc.!

  • 2
    $\begingroup$ The WZ-method provides an algorithm for verifying any identities like this (assuming they're true) from a wide class. en.wikipedia.org/wiki/Wilf–Zeilberger_pair $\endgroup$ – Greg Martin Dec 26 '15 at 6:39

The identity $$ \begin{align} \sum_{s=1}^{m}{2s\choose s}{s\choose m-s}\frac{(-1)^s }{s+1}H_{s}^{(2)}=\frac{2(-1)^m}{m+1}\sum_{s=1}^m H_{s}^{(2)}. \tag{1} \end{align} $$ is equivalent to the following identity $$ \sum_{s=1}^{m}{2s\choose s}\frac{H_s^{(2)}}{s+1}(x-x^2)^s=\frac{2\text{Li}_2(x)}{1-x}-\frac{\ln^2(1-x)}{x},\tag{2} $$ where $\text{Li}_2$ is dilogarithm function. To prove this, first note that $$ \sum_{s=1}^m H_{s}^{(2)}=\sum_{s=1}^m \sum_{k=1}^s \frac{1}{k^2}=\sum_{k=1}^m \frac{1}{k^2}\sum_{s=k}^m 1=\\ \sum_{k=1}^m \frac{1}{k^2}(m+1-k)=(m+1)H_{m}^{(2)}-H_{m}^{(1)}. $$ Now using the generating functions (see link1, link2) $$ \sum_{m=1}^\infty \frac{H_{m}^{(1)}}{m+1}x^m=\frac{\ln^2(1-x)}{2x},\qquad \sum_{m=1}^\infty H_{m}^{(2)}x^m=\frac{\text{Li}_2(x)}{1-x} $$ and proceeding as in this answer one obtains \begin{align} \sum_{s=1}^{\infty}\binom{2s}{s}\frac{(-1)^s}{s+1}x^s (1+x)^sH_s^{(2)}=&\sum_{m=1}^{\infty}\frac{2(-x)^m}{m+1}\left[(m+1)H_{m}^{(2)}-H_{m}^{(1)}\right]=\\ &\frac{2\text{Li}_2(-x)}{1+x}-\frac{\ln^2(1+x)}{-x} \end{align} which is equivalent to $(2)$.

$\bf{Proof\ of\ eq.(2)}$ The generating function of Catalan numbers $$ f(x)=\sum_{n=0}^\infty {2n\choose n}\frac{x^n}{n+1}=\frac{1-\sqrt{1-4x}}{2x}.\tag{3} $$ The generating function of ${2s\choose s}\frac{H_s^{(2)}}{s+1}$ can be obtained from $(3)$ by integrating the identity $$ \frac{f(x)-f(xy)}{1-y}=\sum_{n=1}^\infty {2n\choose n}\frac{x^n}{n+1}(1+y+...+y^{n-1}) $$ as follows \begin{align} \sum_{s=1}^{m}{2s\choose s}\frac{x^s}{s+1}H_s^{(2)}=&\int_0^1\frac{dt}{t}\int_0^t \frac{f(x)-f(xy)}{1-y}dy=\\ &\int_0^1\frac{dt}{t}\int_0^t\frac{dy}{1-y}\left(\frac{1-\sqrt{1-4x}}{2x}-\frac{1-\sqrt{1-4xy}}{2xy}\right)=\\ &-\int_0^1\frac{\ln t}{1-t}\left(\frac{1-\sqrt{1-4x}}{2x}-\frac{1-\sqrt{1-4xt}}{2xt}\right)dt \end{align} [the last line follows after integrating by parts with respect to $t$]. After substitution $\sqrt{1-4xt}=u$ this last integral becomes $$ \frac{\pi^2}{6}\cdot \frac{1-\sqrt{1-4x}}{2x}+4\int\limits_{\sqrt{1-4x}}^1\frac{\ln\frac{1-y^2}{4x}}{(1+y)(y^2-1+4x)}ydy. $$ So after replacing $x$ with $x-x^2$ one obtains $$ \sum_{s=1}^{m}{2s\choose s}\frac{(x-x^2)^s}{s+1}H_s^{(2)}=\frac{\pi^2}{6(1-x)}+4\int\limits_{1-2x}^1\frac{\ln\frac{1-y^2}{4x(1-x)}}{(1+y)(y^2-(1-2x)^2)}ydy $$ This last integral can be calculated by Mathematica in terms of dilogarithm functions, or manually after expanding $\frac{y}{(1+y)(y^2-(1-2x)^2)}$ into partial fractions. Then using functional equations for dilogarithm I verified that the resulting expression equals $\frac{2\text{Li}_2(x)}{1-x}-\frac{\ln^2(1-x)}{x}$.

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.